Complexity–consistency trade‐off in multi‐attribute decision making for vertical handover in heterogeneous wireless networks. Issue 1 (1st January 2016) - Chinnappan, Amali; Balasubramanian, Ramachandran
Abstract : The future wireless communication systems require an intelligent and service adaptive network selection to perform vertical handover (HO) in heterogeneous environments. Since multiple parameters are considered to select the best suitable network, reducing the complexity in multi‐attribute decision making algorithm becomes apparent. In the proposed scheme, fuzzy logic controllers are used to estimate the necessity of HO and to determine the user satisfaction degree based on the critical parameters, such as mobile terminal speed, network load and service cost. Fuzzy analytic hierarchy process is used to calculate the weights of each attribute according to the traffic. Since it handles the uncertainty and vagueness in mapping the user preference to the priority scales, consistency level of network selection can be improved. Quality of service factor is calculated for each network by processing the weighted decision matrix using principal component analysis. Simulation results show that proposed scheme can ensure the best network selection by providing trade‐off between complexity and consistency.